2016
DOI: 10.1111/bjh.14156
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of macromolecular damage are correlated with increased nitric oxide synthase expression in erythrocytes isolated from twin neonates

Abstract: SummaryPregnancy is a state associated with an enhanced metabolism and demand for O 2 , which may lead to the overproduction of reactive oxygen species (ROS) and hence to oxidative stress. An elevated ROS level may result in delayed development and a low birth weight. The aim of this study was to reveal the consequences of multiple pregnancies on the redox status of neonatal human red blood cells (RBCs) and evaluate the role of endothelial nitric oxide synthase (NOS3) -expressing RBCs in the generation of oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Primarily, the NOS3 dimer formation and its phosphorylation at serine1177 residue are crucial criteria in the functional activation of NOS3 [ 17 ]. In accordance with our previous findings and recent publications, endogenous or the acquired exogenous antioxidant defense mechanisms are not fully functional, as the expression of genes coding for antioxidants are downregulated in the twin neonates with comparison to singletons [ 25 ]. On this background, the homeostatic balance between the prooxidant and antioxidant gets easily disrupted and the presence of excess ROS highly influence and regulate the NOS3 activation pathway by the induction of Arginase1 expression.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Primarily, the NOS3 dimer formation and its phosphorylation at serine1177 residue are crucial criteria in the functional activation of NOS3 [ 17 ]. In accordance with our previous findings and recent publications, endogenous or the acquired exogenous antioxidant defense mechanisms are not fully functional, as the expression of genes coding for antioxidants are downregulated in the twin neonates with comparison to singletons [ 25 ]. On this background, the homeostatic balance between the prooxidant and antioxidant gets easily disrupted and the presence of excess ROS highly influence and regulate the NOS3 activation pathway by the induction of Arginase1 expression.…”
Section: Discussionsupporting
confidence: 92%
“…In that situation, NO plays an exceptionally crucial role in the process of vasorelaxation and sufficient blood supply to the fetus. In our previous study, we demonstrated an elevated NOS3 expressing population of RBCs in twin neonates compared to singletons [ 25 ]. Based on the data by Pernow et al [ 23 , 24 ], in the present study we looked for a cross-talk between circulating RBCs and vascular endothelium and focused on the detailed molecular mechanism of NO production not only limited to the RBC population, but also in the UC endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione, for example, needs to be recycled (when oxidized) by glutathione reductase, an NADPH-dependent enzyme, and catalase is also NADPH-dependent to avoid inactivation [19]. Moreover, NADPH oxidase or inducible nitric oxide synthase (eNOS) activities are dependent on NADPH in the erythrocyte [20].…”
Section: Introductionmentioning
confidence: 99%
“…During long-term oxidative stress conditions like twin pregnancy, mapping the efficacy of the NOS pathway becomes pivotal in the regulation of bioavailable NO for vasorelaxation and free flow of blood supply within the cord vascular system. Previously, our working group pioneered in demonstrating an increased ROS production and compromised antioxidant system in parallel with the increased level of NOS3, leading to elevated macromolecular damage in the foetal RBCs of the twin neonates (Dugmonits et al, 2016). Therefore, now in a detailed comparative study, we attempted to elucidate the significance of intimate crosstalk in between the foetal RBCs and the cord vascular endothelium that involves the signalling pathway of NOS3 activation.…”
Section: Discussionmentioning
confidence: 99%